Standard Value of Lower Extremity Muscle Strength of 8 Years Old Children and Its Correlation with Body Weight and Height - Sarifitri FH Hutagalung; Ferial Hadipoetro Idris; Luh K Wahyuni (Indonesian Journal of Physical Medicine & Rehabilitation, 2013)
Objectives: to know the standard value of lower extremity muscle strength of eight year old children and furthermore to explore the correlation of the muscle strength and body height and weight.Methods: The study design is cross sectional. The target is eight year old children in public elementary school in Jakarta Pusat. The subjects’ characteristics are normal nutritional state, and no neurological normusculoskeletal disorders. Sampling was done by cluster randomization to determine the location and simple randomization on site to determine subjects. There were 171 boys and 180 girls in this tudy. Independentvariables are age, sex, body weight, body height and nutritional state that was determine with Z-score of body mass index. Dependent variables are lower extremity muscle strength that classify as torque. This study usedhand-held dynamometer for muscle strength measurement. Statistical analysis was done with descriptive statistic and Pearson and Spearman correlation test.Results: Standard values of eight year old boy’s lower extremity muscle strength are: right hip flexor 21.86 Nm (SD 3.40), left hip flexor 19.64 Nm (SD 3.19), right hip extensor 17.05 Nm (SD 3.66), left hip extensor16.08 Nm (SD 3.56), right knee extensor 18.19 Nm (SD 3.60), left knee extensor 16.09 Nm (SD 3.55), right knee flexor 15.18 Nm (SD 4.23), left knee flexor 14.48 Nm (SD 3.97), right ankle dorsiflexor 6.58 Nm (SD1.53), left ankle dorsiflexor 6.05 Nm (SD 1.42), right ankle plantarflexor 10.08 Nm (SD 1.69), left ankle plantar flexor 9.13 Nm (SD 1.90).Standard values of eight year old girl’s lower extremity muscle strength are: right hip flexor 21.60 Nm (SD 3.62), left hip flexor 19.62 Nm (SD 3.37), right hip extensor 16.66 Nm (SD 4.06), left hip extensor 15.81 Nm(SD 3.94), right knee extensor 17.43 Nm (SD 3.79), left knee extensor 15.20 Nm (SD 3.38), right knee flexor 14.61 Nm (SD 4.28), left knee flexor 13.51 Nm (SD 4.00), right ankle dorsiflexor 6.34 Nm (SD 1.45), leftankle dorsiflexor 5.97 Nm (SD 1.52), right ankle plantarflexor 9.55 Nm (SD 1.98), left ankle plantar flexor 8.69 Nm (SD 1.83). The boy’s lower extremity muscle strength are stronger than the girl’s in left knee extensor,left knee flexor, right ankle plantarflexor and left ankle plantarflexor. The boy’s muscle strength are moderately correlated to body height except for right hip extensor, left hip extensor and right ankle dorsiflexorthat weakly correlated. The boy’s muscle strength are moderately correlated to body weight except for left hip extensor that weakly correlated. The girl’s muscle strength are moderately correlated to body height. Thegirl’s muscle strength are moderately correlated to body weight except for left hip flexor and left hip extensor that weakly correlated.Conclusions: The muscle strength pattern of boys and girls is similar; the strongest are right hip flexor and the weakest are left ankle dorsiflexor.Keywords: Muscle strength, standard values of eight year old children, torque, hand-held dynamometer